A series of 3D lanthanide coordination polymers decorated with a rigid 3, 5-pyridinedicarboxylic acid linker: syntheses, structural diversity, DFT study, Hirshfeld surface analysis, luminescence and magnetic properties. Issue 35 (16th August 2018) - Kumar, Manesh; Kariem, Mukaddus; Sheikh, Haq Nawaz; Frontera, Antonio; Seth, Saikat Kumar; Jassal, Amanpreet Kaur
Abstract : Solvothermal synthesis of six novel coordination polymers of Ln(iii ) containing 3, 5-pyridinedicarboxylic acid. Abstract : Single crystal X-ray diffraction studies reveal the formation of six new coordination polymers (CPs) with the general formulas [Dy(3, 5-pdc)(3, 5-pdcH)(H2 O)2 ] n · n H2 O (1 ), [Pr2 (3, 5-pdc)3 (H2 O)2 ] n ·2 n (H2 O) (2 ), [Sm2 (3, 5-pdc)3 (H2 O)3 ] n · n H2 O (3 ), [Eu2 (3, 5-pdc)3 (H2 O)3 (CH3 CHO)] n · n [2(H2 O)(DMF)] (4 ), [Gd2 (3, 5-pdc)3 (H2 O)2 ] n ·2 n H2 O (5 ) and [Er(3, 5-pdc)(adip)0.5 (H2 O)] n (6 ) (where 3, 5-pdc 2− = fully deprotonated; 3, 5-pdcH − = partially deprotonated 3, 5-pyridinedicarboxylic acid; adip 2− = fully deprotonated adipic acid; and DMF = dimethylformamide) by solvothermal self-assembly of lanthanide ions with rigid 3, 5-pyridinedicarboxylic acid as a linker and adipic acid as an auxiliary flexible spacer (only coordinated in CP6 ). CPs1 and2 crystallize in the triclinic P 1̄ space group, whereas CPs3, 4 and6 crystallize in the monoclinic P 21 / n, P 21 / c and C 2/ c space groups, respectively. CP5 exhibits the trigonal R 3 space group. The 3, 5-pdc ligand exhibits eight diverse coordination modes in CPs1–6, whereas the adipic acid spacer in CP6 shows only one coordination mode (μ4 –κO:κO, O:κO:κO, O). The organic ligands interconnect with metal ions to generate 3D metal–organic frameworks with a variety of intriguing topologies. Theoretical studies, DFT calculations and Hirshfeld surface analysis support the structures adopted by the various CPs. CPs3 (Sm) and4 (Eu) emit strong ligand-sensitized characteristic f – f luminescence. Weak ferromagnetic interactions have been studied at low temperatures for CP1 and CP5 .